Hyperinsulinemia alters insulin receptor presentation and internalization in brain microvascular endothelial cells. (14th August 2022) - Watson, Luke S; Wilken-Resman, Brynna; Williams, Alexus; DiLucia, Stephanie; Sanchez, Guadalupe; McLeod, Taylor L; Sims-Robinson, Catrina
Insulin receptors are internalized by endothelial cells to facilitate their physiological processes; however, the impact of hyperinsulinemia in brain endothelial cells is not known. Thus, the aim of this study was to elucidate the impact hyperinsulinemia plays on insulin receptor internalization through changes in phosphorylation, as well as the potential impact of protein tyrosine phosphatase 1B (PTP1B). Hippocampal microvessels were isolated from high-fat diet fed mice and assessed for insulin signaling activation, a process known to be involved with receptor internalization. Surface insulin receptors in brain microvascular endothelial cells were labelled to assess the role hyperinsulinemia plays on receptor internalization in response to stimulation, with and without the PTP1B antagonist, Claramine. Our results indicated that insulin receptor levels increased in tandem with decreased receptor signaling in the high-fat diet mouse microvessels. Insulin receptors of cells subjected to hyperinsulinemic treatment demonstrate splice variation towards decreased IR-A mRNA expression and demonstrate a higher membrane-localized proportion. This corresponded with decreased autophosphorylation at sites critical for receptor internalization and signaling. Claramine restored signaling and receptor internalization in cells treated with hyperinsulinemia. In conclusion, hyperinsulinemia impacts brain microvascular endothelial cell insulin receptor signaling and internalization, likely via alternative splicing and increased negative feedback from PTP1B.